The Influence of Flash Sale on Impulsive Buying Behavior Through the Shopee E-Commerce Application in PIPS FKIP University of Riau Students - Erlina Manurung; Sri Kartikowati; Hendripides Hendripides (Journal of Education Technology Information Social Sciences and Health, 2024)
The purpose of this study is to analyze the effect of flash sales on impulse buying behavior through the Shopee e-commerce application with the target of 126 students majoring in PIPS FKIP Universitas Riau class of 2021 as a research sample determined based on purposive sampling techniques. By using quantitative descriptive methods. The data were collected using a questionnaire instrument and analyzed with the T test. The results obtained were 0.000 α 0.05, so it can be concluded that there is a positive and partially significant influence between partial flash sales on impulse buying behavior in students majoring in PIPS FKIP Riau University.